The Role of Women in Political Participation in Cambodia: A Case Study of Svay Rieng Province - PEN, Dina; Dy, Putheara; Ros, Ravuth; EM, Sereyrath; Nut, Vatheana (Journal of Mathematics Instruction, Social Research and Opinion, 2024)
The government considers women as the backbone of Cambodia's economy and society. Despite a good sign, the female parliamentary representation in Svay Rieng fluctuated in the last three mandates (60% in 2008 and 2013, 80% in 2018, and 60% in 2023). The study aims to investigate the “socioeconomic”, “traditional-cultural”, “family”, and “personal” factors affecting gender roles in political involvement in Svay Rieng province, to assess perceptions and attitudes regarding women's political engagement. A mixed-methods approach was utilized, administering surveys to 119 participants and semi-structured interviews with 8 women actively participating in politics and leadership roles, using snowball sampling. The findings emphasize 1) Family-factors (domestic responsibilities, violence, and lack of support) hinder women's political participation the most, 2) Personal factors: limited education and self-confidence, 3) Socio-economic obstacles (the social devaluation of women, violence against women, limited outreach initiatives, and the impact of economic crises), and 4) Traditional customs, cultural norms including prescribed gender roles further contribute to the challenges faced by women in politics. Despite these obstacles, the study identifies positive perceptions and attitudes towards women's political participation. Participants underlined the need to empower women at both the national and sub-national levels, as well as fostering capacity development and extending possibilities. The recommendations include adopting gender equality legislation, increasing awareness, improving capacity-building programs, providing supportive infrastructure, engaging male allies, promoting cooperation, and assuring long-term commitment. A future study should look at additional elements that may impact women's political engagement, as well as evaluate the efficiency of existing policies for empowering women in Svay Rieng.